Analisis Materi Bahasa Prancis Perhotelan dan Restorasi pada Laman LingoHut untuk Mata Kuliah Français de l’Hôtellerie et de la Restauration - Azilia Sawitri; Iim Siti Karimah; Yadi Mulyadi (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to evaluate the suitability of the LingoHut language learning website as a self-learning medium for students of Français de l’Hôtellerie et de la Restauration. This is motivated by the need for verified learning media, given that popular websites may not necessarily meet professional standards. This study uses a qualitative descriptive method with a two-layer content analysis design. The research data source is the LingoHut website, while data collection techniques were conducted through observation and documentation of the available content and features. Data analysis was carried out systematically. First, the website content was mapped against the DFP (Diplôme de Français Professionnel) Tourism-Hospitality-Catering competency standards to assess the scope of the material. Second, the website's presentation design was analyzed for its alignment with the principles of Mayer's Multimedia Learning Theory, particularly regarding cognitive efficiency. The results of the study indicate that LingoHut's content support is partial, limited to basic vocabulary enrichment, and thus does not cover all the required competencies. The multimedia design has positive potential in terms of user control (Segmentation Principle), but is limited in cognitive efficiency due to violating the Redundancy Principle. As data validation, these findings confirm that LingoHut has potential as a supplementary medium but is insufficient as the primary learning source to achieve comprehensive French language competencies in the hospitality and restaurant industry.